Intimate Partner Violence During Pregnancy in South Asia: Systematic Review and Meta-Analysis - Nepal, Samata; Atreya, Alok; Shrestha, Dhan Bahadur; Budhathoki, Pravash; Lamichhane, Samit; Nepal, Sarbin; Marahatta, Achyut; Dhital, Rolina (Journal of Nepal Health Research Council, 2023)
Background: This systematic review collated the literature on the prevalence rate of different types of intimate partner violence (IPV) during pregnancy in South Asia. Methods: Systematic literature searches were conducted in four major databases (Embase, Scopus, PubMed, PubMed Central) to identify relevant articles published from the inception of each database to May 2021, which reported data on the prevalence of intimate partner violence during pregnancy in South Asia. The Joanna Briggs Institute critical appraisal tool for prevalence studies was used to assess the risk of bias in individual studies. A random-effects model was used to calculate the pooled prevalence and corresponding 95% confidence interval due to significant between-study heterogeneity. Results: Thirty-seven studies were reviewed which showed an overall prevalence of IPV from South Asian countries was 23.4% (physical violence: 13.6%; sexual violence: 8.5%; emotional violence: 20.2%). Conclusions: There was a higher prevalence of intimate partner violence during pregnancy reported, with an overall prevalence ranging from 1.7% to 66.4% across studies. Emotional violence was more prevalent form when compared to sexual or physical violence. Keywords: Intimate partner violence; pregnancy, south Asia; systematic review.